Complementarities between barriers to innovation: Data evidence from Poland - Anna Wziątek-Kubiak; Marek Pęczkowski; Ewa Balcerowicz (Center for Social and Economic Research (CASE), 2010)
This paper investigates the barriers to innovation perceived by Polish manufacturing firms. It refers to the heterogeneity of innovation active firms. We introduce a taxonomy of innovative firms based on the frequency with which they introduce commercialised innovations using data from both CIS4 (for 2002-2004) and CIS5 (2004-2006). Two groups of innovation-active firms are distinguished: those which introduced innovation in both periods covered by both CIS (which we call persistent innovators) and those which introduced innovation either in CIS4 or CIS5 (which we call occasional innovators). We use a four step analysis covering binary correlations, Principal Component Analysis, probit model and correlations of disturbances. Two types of explanatory variables describing firms' characteristics and innovation inputs used are considered. The paper shows that there are considerable differences in sensitivities to the perception of innovation barriers and in complementarities among barriers between persistent and occasional innovators. In the case of occasional innovators, a kind of innovation barrier chain is observed. This has an impact on differences in the frequency of innovation activities between the two groups of innovators and results in a diversification of innovators.
Keywords: O31; O32; O33; D21; D83; 330; Innovation of the firms; Barriers to innovation; Innovation sources; New Member States; Complementarity; Innovation; Innovationsmanagement; Industrie; Polen